POTENSI EKSTRAK DAUN TANAMAN KARAMUNTING (Melastoma malabathricum L.) DI DAERAH KALIMANTAN SEBAGAI ANTIBAKTERI Staphylococcus aureus - Rakhmadhan Niah; Riki Nirwan Baharsyah (Jurnal Ilmiah Manuntung, 2018)
The year 2008 recorded the death toll reached 16,769 soul due to infection. Infection is one of the diseases caused by bacteria or parasites. Staphylococcus aureus is one of the bacteria causes infection of the skin that is often the case in Indonesia. Staphylococcus aureus bacterial infection can be treated naturally, one of the plants that can be utilized is plant karamunting. Plant leaf karamunting (Melastoma malabathricum l.) contain flavonoids and alkaloids that have activity as antibacterial. The purpose of this research is to know the power of drag karamunting folium of extract against the growth of Staphylococcus aureus. In vitro studies were conducted with diffusion agar method. The extraction of leaf maceration method done with karamunting solvent ethanol 96%. Concentration of karamunting folium of extract used are: 25%, 50%, 75%, and 100%. Microbiology research results indicate that karamunting folium of extract have drag against the growth of bacteria Staphylococcus aureus with extract concentration 50% yield of 5.34 mm; the concentration of extract 75% of 9.40 mm; the concentration of extract 100% of 12.43 mm.